PENGARUH PERENCANAAN ANGGARAN, KOMPETENSI SUMBER DAYA MANUSIA, PELAKSANAAN ANGGARAN DAN PEGAWASAN TERHADAP PENYERAPAN ANGGARAN MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Andarias Patiran; Melyanus Bonsapia (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
This study conducts budget planning planning, budget competence and oversight of budget absorption through the moderating variable organization in the Jayapura district government. Examiners were carried out on a sample of 89 respondents. The sample method used was purposive sampling. Data is done by direct survey. Hypothesis testing is tested empirically using moderated regression. The results showed that budget planning had no effect on the regency budget of jayapura, human resource competence had an effect on budget absorption of the regency of jayapura, budget execution had no effect on the regency budget of jayapura, supervision had an effect on the budget of the regency of jayapura, organizational commitment did not moderate budget planning on budget provision the regency of jayapura, the organizational commitment to moderate the competence of human resources towards the absorption of the jayapura regency budget, the organizational commitment to moderate the implementation of the jayapura district budget and the organizational commitment did not moderate the supervision of the budget absorption of the jayapura regency